Posttransplant cyclophosphamide-based anti-graft-vs-host disease prophylaxis in patients with acute lymphoblastic leukemia treated in complete remission with allogeneic hematopoietic cell transplantation from human leukocyte antigen-mismatched unrelated donors versus haploidentical donors: A study on behalf of the ALWP of the EBMT - Nagler, Arnon; Labopin, Myriam; Arat, Mutlu; Reményi, Péter; Koc, Yener; Blaise, Didier; Angelucci, Emanuele; Vydra, Jan; Kulagin, Aleksandr; Socié, Gerard; Rovira, Montserrat; Sica, Simona; et al. (Cancer, 2022)
BACKGROUND: Both mismatched unrelated donor (MMUD) and haploidentical (haplo) transplantation are valid options in patients with high-risk acute lymphoblastic leukemia (ALL) lacking a matched donor. METHODS: The study compared the outcomes of adult patients with ALL in complete remission (CR) who underwent 9/10 MMUD versus haplo transplantation with posttransplant cyclophosphamide (PTCy) as graft-vs-host disease (GVHD) prophylaxis in 2010-2020. RESULTS: The study included 781 patients (MMUD, 103; haplo, 678). The median age was 40 (19-73) and 38 (18-75) years, respectively (p = .51). The most frequent immunosuppression agents added to PTCy were mycophenolate mofetil (MMF)/cyclosporine A and MMF/tacrolimus. In vivo T-cell depletion (anti-thymocyte globulin) was administered to 21% and 8% of the transplants, respectively (p < .0001). Neutrophil (absolute neutrophil count >0.5 × 109 /L) recovery was achieved in 97.1% versus 96.7% versus (p = 1) in MMUD and haplo, respectively. Nonrelapse mortality and relapse incidence were not significantly different between MMUD and haplo, hazard ratio (HR) = 1.45 (95% confidence interval [CI], 0.81-2.62; p = .21) and HR = 0.81 (95% CI, 0.52-1.28, p = .38), respectively. HRs for leukemia-free survival, overall survival, and GVHD-free, relapse-free survival were respectively, HR = 1.05 (95% CI, 0.73-1.50, p = .8), HR = 1.17 (95% CI, 0.77-1.76, p = .46), and HR = 1.07 (95% CI, 0.78-1.46, p = .7) for haplo compared to MMUD. Acute (a)GVHD grade 2-4 was significantly higher with haplo, HR = 1.73 (95% CI, 1.08-2.76, p = .023), whereas aGVHD grade 3-4 and chronic GVHD did not differ significantly between the two transplant groups. CONCLUSION: Outcomes of MMUD and haplo transplants with PTCy-based GVHD prophylaxis for ALL patients in CR are similar, apart from a higher incidence of aGVHD with haplo transplants.
Keywords: dospělí; Mycophenolic Acid; Cyclophosphamide; akutní lymfatická leukemie; Acute Disease; Adult; graft versus host disease; allogeneic stem cell transplantation; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Transplantation Conditioning; mismatched unrelated donors; retrospektivní studie; posttransplant cyclophosphamide; haploidentical; kyselina mykofenolová; Unrelated Donors; nemoc štěpu proti hostiteli; HLA antigeny; akutní nemoc; Precursor Cell Lymphoblastic Leukemia-Lymphoma; acute lymphoblastic leukemia; nepříbuzný dárce; HLA Antigens; Retrospective Studies; cyklofosfamid; Graft vs Host Disease; Humans